Association of various lipid parameters with premature coronary artery disease in men - A. V. Tyurina; O. I. Afanas’eva; E. A. Klesareva; N. A. Tmoyan; O. A. Razova; M. V. Ezhov; S. N. Pokrovsky (Российский кардиологический журнал, 2022)
Aim. To assess the relationship between premature coronary artery disease (CAD) and various lipid parameters.Material and methods. This retrospective longitudinal study included 166 men aged 57±9 years with coronary CAD with onset before age of 55. The control group consisted of 62 men (60±8 years old) who did not have CAD and peripheral arterial disease. In all patients, data on following lipid profile parameters were collected: total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), non-high-density lipoprotein cholesterol (non-HDL-C) and lipoprotein(a) (Lp(a)) at the time of CAD onset, while in control group patients — at the first visit to the A.L. Myasnikov Institute of Clinical Cardiology. These indicators were measured in blood plasma at the time of enrollment in all patients. In addition, the concentration of LDL-C corrected for Lp(a)-cholesterol (LDL-Ccorr) was calculated. Hypercholesterolemia was diagnosed with an initial level of TC >5 mmol/l, or LDL-C ≥3,0 mmol/l, or non-HDL-C ≥3,8 mmol/l, while hyperlipoproteinemia(a) (HLP(a)) — at the level of Lp(a) ≥30 mg/dl.Results. Lipid metabolism disorders were significantly more common in patients with premature CAD compared to the control group. Lp(a) concentration ≥30 mg/dl, along with elevated levels of non-HDL-C or LDL-Ccorr, were associated with premature CAD, regardless of heredity and smoking, in the general cohort of examined men. Kaplan-Meier survival analysis showed that any type of lipid metabolism disorder was associated with an increased risk of premature CAD. In addition, patients with isolated elevated Lp(a) concentrations lived to the CAD onset 8 years earlier — 47 vs 55 years, p<0,02. The probability of premature CAD was maximum when the elevated level of non-HDL-C and HLP(a) was combined (hazard ratio, 2,91 (95% CI 1,96-4,33), p<0,0001).Conclusion. HLP(a) is an independent factor of premature CAD, even with normolipidemia, which confirms the need for routine measurement of Lp(a) in clinical practice.